"They made me feel like a teacher rather than a praccie": sinking or swimming in pre-service drama education. Issue 2 (15th March 2019) - Gray, Christina; Wright, Peter; Pascoe, Robin
ABSTRACT: Support, professional guidance and modelling of teaching practice offered by quality mentor teachers are important components in preparing teachers for the profession. Yet research confirms the impact of poor mentoring on pre-service teachers' developing pedagogy. This paper reports findings from a qualitative study with pre-service drama teachers and their mentors as a way of better understanding how mentoring impacts their developing pedagogy, in a learning area that is highly interactive and relational. Data comprised of observations of planning and teaching, participant interviews, journals and field notes representing five pre-service drama teachers' experience of mentors during an extended teaching practicum. These data revealed the considerable variance and disparities in mentoring styles and quality and the repercussions for the pre-service drama teachers. The discussion addresses the implications of these findings in light of those mentor attributes identified as most conducive to creating competent and confident beginning drama teachers.